1978
DOI: 10.1002/ange.19780900407
|View full text |Cite
|
Sign up to set email alerts
|

Kernresonanzspektroskopie mit Natrium-23

Abstract: Die Entwicklung der Fourier-Transform-Tehnik hat die 23Na-NMR-Spektroskopie zu einem wichtigen Hillsmittel werden lassen, mit dem der Organiker wie der Bio-Anorganiker Phanomene der Solvatation und der Ionenpaar-Bildung direkt beobachten kann. Die chemische Verschiebung und die Linienbreite von 23Na-Signalen erschliekn Komplexstabilitatskonstanten, Korrelationszeiten von Reorientierungsvorgangen und die Mikrodynamik in der Koordinationssphare des Natrium-Ions. In Konkurrenzexperimenten konnen mit der 23Na-NMR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(3 citation statements)
references
References 189 publications
0
3
0
Order By: Relevance
“…These questions are answered using a combination of , 13C, and 31P NMR, and the corresponding heteronuclear Overhauser effects, together with direct examination of alkali metal nuclear magnetic resonance. 40,41 The first article is devoted to an examination of the selfassembly of the sodium salt of guanylic acid, i.e., S'-GMP. In the accompanying article,42 we describe results obtained in the presence of other cations besides sodium, especially K+ and NH4+.…”
Section: Introductionmentioning
confidence: 99%
“…These questions are answered using a combination of , 13C, and 31P NMR, and the corresponding heteronuclear Overhauser effects, together with direct examination of alkali metal nuclear magnetic resonance. 40,41 The first article is devoted to an examination of the selfassembly of the sodium salt of guanylic acid, i.e., S'-GMP. In the accompanying article,42 we describe results obtained in the presence of other cations besides sodium, especially K+ and NH4+.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with halide ion NMR studies of protein-anion interactions, very few NMR studies of protein interactions with the alkaline and alkaline earth cations have been reported. (A brief review of 23Na+ NMR studies has recently been given by Laszlo (1978) and on 23Na and 39K NMR in biological systems by Civan and Shporer, 1978). There are probably several reasons for this situation.…”
Section: A General Introductionmentioning
confidence: 99%
“…It was on this basis that the dependence of δ ( 23 Na) on DN, expressing the electron donating power of a Lewis base, was explained 6. In his 1978 review on 23 Na NMR spectroscopy,14 Laszlo pointed out that this conclusion was quite paradoxical considering that the charge transfer (or the covalent contribution to bonding) from the ligand (or solvent molecule) to Na + was very small. More recent calculations on charge transfer from neutral molecules toward alkali metal cations15 do not contradict this judgment.…”
mentioning
confidence: 99%